International Opportunity Recognition of Entrepreneurs from Emerging Economies: Evidence from Indonesia - Astuti, Novika Candra (CENTRAL ASIA AND THE CAUCASUS, 2022)
International opportunity recognition is the fundamental concept to the field of international entrepreneurship (IE), yet the extant literature has limited of empirical studies in this area. This study employs five cases of internationalizing Indonesian SMEs in creative industries. The purpose of this study to examine factors that lead to the recognition of international opportunities. The paper finds that prior business experience, knowledge of international markets, social and business networks, serendipity, and innovativeness drive entrepreneurs to recognize international opportunities.